The role of antibiotics in patients with increased risk of infection during extracorporeal shock wave lithotripsy (ESWL) treatment - (:unkn) unknown (My University, 1996)
Objective. In this prospective, randomized study, the incidence of urinary tract infections following extracorporeal shock wave lithotripsy (ESWL) in a high risk population and effectiveness of two different antimicrobial agents were evaluated. Methods: A total of 56 patients with renal and ureteric stones who had increased risk of infection before ESWL treatment received either 200 mg of Ofloxacin or trimethoprim-sulfamethaxazole (TM+SMZ) 160/400 mg. bid. Patients were followed by simple urine analysis, urine cultures and blood cultures if necessary together with clinical evaluations. Results: Three patients (5.4%) had positive urine cultures one week after ESWL. The incidence of positive cultures was 40% in patients who had asymptomatic bacteriuria before ESWL. Conclusion: The urine should be sterilized by appropriate antibiotic administration before initiation of ESWL therapy in patients with bacteriuria to prevent infectious complications.
Keywords: Antibiotics; Infection; Lithotripsy; Risk factors